Classification of oil–particle interactions in aqueous environments: Aggregate types depending on state of oil and particle characteristics. (August 2018) - Boglaienko, Daria; Tansel, Berrin
Abstract: There are significant differences in the aggregation mechanisms and types of aggregates that form by oil-particle interactions in marine and laboratory environments depending on the state of oil (i.e., dissolved, emulsified, floating), size and type of particles involved (i.e., colloidal, granular, organic, inorganic), oil-particle interaction mechanisms, and settling/suspension characteristics. Distinct characteristics of oil-particle aggregates that form by interaction of granular particles with floating oil separate them from the well-known oil-colloidal particle aggregates (OcPA), which are sometimes called Pickering emulsions. Unlike OcPA, which involve emulsified oil (entrained oil droplets suspended in the water column) and colloidal particles, the oil-granular particle aggregates (OgPA) involve the floating oil and granular particles. Here, to clarify the differences and similarities between the two types of aggregates (OcPA and OgPA), we present classification of oil aggregates, drawing attention to important characteristics of OcPA, marine oil snow (MOS), and OgPA. Graphical abstract: Unlabelled Image Highlights: Aggregation mechanisms are different depending on particle size on oil state. Oil-colloidal particle aggregates (OcPA) involve emulsified oil and colloidal particles. Oil-granular particle aggregates (OgPA) involve the floating oil and granular particles. Marine snow contains biogenic particles and exhibit different characteristics depending on location. Formation and settling of OcPA, OgPA and marine snow are significantly different.